KUALITAS SARANA PRASARANA DAN DAMPAKNYA TERHADAP MINAT MENGHAFAL SANTRI DALAM PENDIDIKAN TAHFIDZUL QURAN PONDOK PESANTREN HIDAYATULLAH PUTRI KENDARI - Achmad Syahroni; Ismail; Indrawan Tobarasi (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the quality of facilities and infrastructure available at the Hidayatullah Putri Kendari Islamic Boarding School and its impact on students' interest in memorizing the Qur'an. Using a qualitative approach, data were collected through interviews, observations, and documentation studies. The results of the study indicate that good quality facilities and infrastructure contribute positively to students' motivation and interest in the tahfidz process. In addition, this study also found a significant relationship between adequate facilities and students' success in memorizing. These findings are expected to provide recommendations for improving the quality of education in Islamic boarding schools.